2019
DOI: 10.1021/acs.analchem.9b02938
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of Boron and Nitrogen Codoped Green Emission Carbon Quantum Dots for Detection of Permanganate and Captopril

Abstract: A hydrothermal strategy for preparing boron and nitrogen codoped carbon quantum dots was studied using the precursors of p-amino salicylic acid, boric acid and ethylene glycol dimethacrylate. The boron and nitrogen codoped carbon quantum dots have high fluorescence intensity, good monodispersity, high stability, superior water solubility, and a fluorescence quantum yield of 19.6%. Their average size is 5 nm. Their maximum excitation and emission wavelengths are 380 and 520 nm, respectively. Permanganate (MnO 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(35 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…This excitation‐dependent fluorescence emission may be ascribed to their surface defects and different particle sizes. [ 20 ] The quantum yield of N‐CQDs was measured to be 6.4% by referring to quinine sulfate in 0.1 M H 2 SO 4 (quantum yield = 0.58). The relatively high quantum yield might be caused by the charge density change due to the doping of nitrogen and surface functionalization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This excitation‐dependent fluorescence emission may be ascribed to their surface defects and different particle sizes. [ 20 ] The quantum yield of N‐CQDs was measured to be 6.4% by referring to quinine sulfate in 0.1 M H 2 SO 4 (quantum yield = 0.58). The relatively high quantum yield might be caused by the charge density change due to the doping of nitrogen and surface functionalization.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that the abnormal level of l ‐AA was related to various diseases such as cardiovascular diseases, urinary stones, and cancers and so on. [ 17,18 ] Therefore, numerous tactics have been explored for the detection of MnO 4 − and l ‐AA, such as electrochemistry, [ 18,19 ] colorimetric detection, [ 16,17 ] fluorometry [ 20 ] and so on. Among these methods, fluorometry has been more widely adopted due to its simple operation, fastness, high sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] CQDs have reportedly been used as fluorescent probes for detecting CP. In 2019, Jiang et al [19] reported highly photoluminescent boron-nitrogen codoped CQDs (B,N-CQDs), which were used to develop a simple and environmentally friendly hydrothermal synthesis method through the combined action of p-amino acid, boric acid, and ethylene glycol dimethacrylate (EDMA). MnO 4 À quenches the fluorescence emitted by the B,N-CQDs through self-absorption and static quenching.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Because of their low toxicity, high physicochemical stability, ease of functionalisation, and fluorescent characteristics, and biocompatibility they have garnered substantial research in recent years. [20][21][22][23] Because of these and other features, CQDs have been frequently utilised in electrochemical immune sensing, [24][25][26][27][28][29] bio-imaging, [30][31][32] fluorescent probes, [33][34][35][36][37][38][39][40][41] drug/gene delivery [42] photocatalysis, [43][44][45][46][47] and optoelectronics. [48] CQDs and other quantum dots, such as silicon, phosphorous, germanium, or from compound semiconductor materials, such as CdSe, CdTe, and PbS have been discovered and exhibits strong PLQY, and tuneable photoluminescence in general.…”
Section: Introductionmentioning
confidence: 99%